When Gay People Get Married : What Happens When Societies Legalize Same-Sex Marriage - Badgett, Mary Virginia Lee (Book collections on Project MUSE., 2010)
" ... Badgett offers a rare look at how gay marriage is actually working, by taking readers to a land where it has been legal for same-sex couples to marry since 2001: the Netherlands. Through interviews with married gay couples we learn about the often surprising changes to their relationships, and the reactions of their families and work colleagues. Moreover, Badgett shows how the institution itself has been altered, exploring how the concept of marriage itself has changed in the United States and the Netherlands." "The evidence from around the world shows both that marriage changes gay people more than gay people change marriage and that it is the most liberal countries and states making the first moves to recognize gay couples. In the end, Badgett demonstrates that allowing gay couples to marry does not destroy the institution of marriage and that many gay couples do benefit, in expected as well as surprising ways, from the legal, social, and political rights that the institution offers."--Publisher description.